Negative phototaxis in the photosymbiotic sea anemone Aiptasia as a potential strategy to protect symbionts from photodamage - Kishimoto, Mariko; Gornik, Sebastian G.; Foulkes, Nicholas S.; Guse, Annika (Scientific reports, 2023)
Photosymbiotic cnidarians generally seek bright environments so that their symbionts can be photosynthetically active. However, excess light may result in a breakdown of symbiosis due to the accumulation of photodamage in symbionts causing symbiont loss (bleaching). It is currently unknown if photosymbiotic cnidarians sense light only to regulate spawning time and to facilitate predation, or whether they also use their light-sensing capacities to protect their symbionts from photodamage. In this study, we examined how the sea anemone Aiptasia changes its behaviour when exposed to excess light. We reveal that Aiptasia polyps, when carrying symbionts, contract their bodies when exposed to high light intensities and subsequently migrate away in a direction perpendicular to the light source. Interestingly, this negative phototaxis was only evident under blue light and absent upon UV, green and red light exposure. Non-symbiotic Aiptasia did not exhibit this light response. Our study demonstrates that photosymbiotic Aiptasia polyps display negative phototactic behaviour in response to blue light, and that they also can perceive its direction, despite lacking specialized eye structures. We postulate that Aiptasia uses blue light, which penetrates seawater efficiently, as a general proxy for sunlight exposure to protect its symbionts from photodamage.
Gesehen am 06.12.2023